Diphenyldibenzofulvene‐Based Sensitizers for Efficient Dye‐Sensitized Solar Cells: The Tuned Absorption Properties and Partially Suppressed Aggregation. Issue 2 (29th January 2014) - Li, Huiyang; Tang, Runli; Hou, Yingqin; Yang, Yizhou; Chen, Junnian; Liu, Linfeng; Han, Hongwei; Peng, Tianyou; Li, Qianqian; Li, Zhen
Abstract Three new organic sensitizers (LI‐62, LI‐63, and LI‐64) were designed and synthesized, in which the diphenyldibenzofulvene (DPDBF) π‐bridge was structurally modified by introducing different groups to its phenyl rings to fine‐tune the electronic properties. Accordingly, the light‐harvesting capabilities, energy levels, and photovoltaic performances were systematically investigated. The three‐dimensional configuration of DPDBF can weaken the intermolecular interactions, and, thus, benefit the orderly arrangement of the dyes onto the TiO2 surface. In comparison to LI‐62, which contained the electron‐withdrawing CF3 group as a substituent on the DPDBF moiety, LI‐64 with the electron‐donating SMe group exhibited a higher molar extinction coefficient and IPCE value, which directly led to a higher conversion efficiency and provided some useful information for the optimization of organic dyes that have a high photovoltaic performance.